2009
DOI: 10.1177/0192623309334147
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarsinic Acid in Drinking Water Changed the Morphology of Urinary Bladder but Not the Expression of DNA Repair Genes of Bladder Transitional Epithelium in F344 Rats

Abstract: Inorganic arsenic increases urinary bladder transitional cell carcinoma in humans. In F344 rats, dimethylarsinic acid (DMA[V]) increases transitional cell carcinoma. Arsenic-induced inhibition of DNA repair has been reported in cultured cell lines and in lymphocytes of arsenic-exposed humans, but it has not been studied in urinary bladder. Should inhibition of DNA damage repair in transitional epithelium occur, it may contribute to carcinogenesis or cocarcinogenesis. We investigated morphology and expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In addition, the bladder urothelium of rats showed not only extensive cellular necrosis but evidence of hyperplasia after 10 weeks of treatment with 100 ppm DMA V (Cohen et al, 2001). In the present study, we detected the ultrastructural changes of the organelles in the urothelium of rats by TEM and observed that rats treated with 100 or 200 ppm DMA V increased vacuolation, mitochondria swollen and cytoplasm dissolved and disintegrated in the transitional epithelium, in accordance with Wang et al (2009) results. Together these data indicate that DMA V induced urothelial toxicity and necrosis first, followed by regenerative hyperplasia and proliferation.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the bladder urothelium of rats showed not only extensive cellular necrosis but evidence of hyperplasia after 10 weeks of treatment with 100 ppm DMA V (Cohen et al, 2001). In the present study, we detected the ultrastructural changes of the organelles in the urothelium of rats by TEM and observed that rats treated with 100 or 200 ppm DMA V increased vacuolation, mitochondria swollen and cytoplasm dissolved and disintegrated in the transitional epithelium, in accordance with Wang et al (2009) results. Together these data indicate that DMA V induced urothelial toxicity and necrosis first, followed by regenerative hyperplasia and proliferation.…”
Section: Discussionsupporting
confidence: 89%
“…43 It can be assumed that the better efficacy of PLGA-loaded tea polyphenols may be due to the enhanced penetration capability of NPs across the cell surface (bulk materials have to face several barriers). 16,17 It is well known that mutations in somatic cells play a central role in cancer initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…In another study using human lung cells [50], the gene expression of DNA ligase I, XPD, XPC, and RFA was found to decrease by at least 2-fold after treatment with 5 mol/L arsenite for 4 h. Interestingly, in SV40-immortalized human keratinocytes (RHEK-1), multiple DNA repair proteins were overexpressed when treated with arsenic alone but suppression of DNA repair protein expression was observed when the cells were treated with an arsenic-containing metal mixture [51]. DMA V , the only methylated metabolite of inorganic arsenic that has been studied in this respect did not change the expression of DNA repair genes, including XPB, of bladder transitional epithelium in F344 rats [52]. Most recently, Nollen et al [53] found that a 24-h treatment with arsenite or MMA III strongly decreased XPC at both the mRNA and protein levels in normal human skin fibroblasts immortalized by telomerase transfection (VH10hTert).…”
Section: Possible Mechanisms Of Ner Inhibition By Arsenic 41 Arsenicmentioning
confidence: 94%